Eficiencia y eficacia administrativa de los Servidores Públicos del Distrito de Educación 13D07 Chone-Flavio Alfaro - Meza Cuadros, Yirian Mishel (2020)
It was carried out with the objective of evaluating the administrative efficiency and effectiveness of the public servants of the Education District 13D07 Chone-Flavio Alfaro for the improvement of their performance, for this reason, scientific and legal theories were established that provided a theoretical basis for the research. Among the activities, the institution's Annual Operational Plan was studied, where it was possible to establish compliance with the objectives and an estimated 12-month schedule based on the budget allocated by the Ministry of Education; however, the allocation of resources is deficient since it does not allow the respective institutional objectives to be met in relation to its indicators. Research techniques such as the interview were used, where the results were: that the institution carries out the application of indicators to verify compliance with the activities of the POA, however, there is no budget increase to carry out each of the proposed activities. Subsequently, the performance of the public servants of the District was measured through management indicators such as efficacy, efficiency and effectiveness, obtaining the following: non-compliance with the administration and provision of goods and services, among others. In this way, with the results obtained, we proceeded to propose actions that improve the efficiency and administrative effectiveness of the institution's public servants such as: having a 100% budget execution to provide the necessary resources for the institution, obtaining efficient management within the goods and services.